Hospital Elder Life Program in the Real World: The Many Uses of the Hospital Elder Life Program Website. Issue 4 (14th April 2015) - Chen, Pei; Dowal, Sarah; Schmitt, Eva; Habtemariam, Daniel; Hshieh, Tammy T.; Victor, Ryan; Boockvar, Kenneth S.; Inouye, Sharon K.
Abstract : The Hospital Elder Life Program (HELP) can prevent delirium, a common condition in older hospitalized adults associated with substantial morbidity, mortality, and healthcare costs. In 2011, HELP transitioned to a web‐based dissemination model to provide accessible resources, including implementation materials; information for healthcare professionals, patients, and families; and a searchable reference database. It was hypothesized that, although intended to assist sites to establish HELP, the resources that the HELP website offer might have broader applications. An e‐mail was sent to all HELP website registrants from September 10, 2012, to March 15, 2013, requesting participation in an online survey to examine uses of the resources on the website and to evaluate knowledge diffusion related to these resources. Of 102 responding sites, 73 (72%) completed the survey. Thirty‐nine (53%) had implemented and maintained an active HELP model. Twenty‐six (35%) sites had used the HELP website resources to plan for implementation of the HELP model and 35 (50%) sites to implement and support the program during and after launch. Sites also used the resources for the development of non‐HELP delirium prevention programs and guidelines. Forty‐five sites (61%) used the website resources for educational purposes, targeting healthcare professionals, patients, families, or volunteers. The results demonstrated that HELP resources were used for implementation of HELP and other delirium prevention programs and were also disseminated broadly in innovative educational efforts across the professional and lay communities.